Interfacial Assemble of Prussian Blue Analog to Access Hierarchical FeNi (oxy)-Hydroxide Nanosheets for Electrocatalytic Water Splitting - Hong, Jinquan; Lv, Jiangquan; Chen, Jialing; Cai, Lanxin; Wei, Mengna; Cai, Guoseng; Huang, Xin; Li, Xiaoyan; Du, Shaowu (Frontiers in Chemistry, 2022)
Developing facile methods for the synthesis of active and stable electrocatalysts is vitally important to realize overall water splitting. Here, we demonstrate a practical method to obtain FeNiOOH nanosheets on nickel foam (NF) as bifunctional electrocatalyst by growing a FeCo Prussian blue analog with further in situ oxidation under ambient conditions. The binder-free, self-standing FeNiOOH/NF electrode with hierarchical nanostructures requires low overpotentials of 260 mV and 240 mV at a current density of 50 mA cm−2 for oxygen evolution reaction and hydrogen evolution reaction, respectively, in 1.0 M KOH solution. Therefore, an alkaline water electrolyzer constructed by bifunctional FeNiOOH/NF electrode as both anode and cathode delivers 50 mA cm−2 under a cell voltage of 1.74 V with remarkable stability, which outperforms the IrO2-Pt/C-based electrolyzer. The excellent performance could be ascribed to the superior FeNiOOH intrinsic activity and the hierarchical structure. This work provides a cost-efficient surface engineering method to obtain binder-free, self-standing bifunctional electrocatalyst on commercial NF, which could be further extended to other energy and environment applications.